INFORMATION SYSTEM FOR PUBLIC PLACES AND INSTITUTIONS VISUALIZATION WITH OPPORTUNITIES OF INCLUSIVE ACCESS AND OPTIMAL ROUTING (Computer systems and information technologies, 2022)
Inclusive access has been considered essential and relevant for decades. However, this issue has been in demand in the past years, both in Europe and Ukraine. One of the popular means of providing inclusive access within the city is information systems that are friendly to people with disabilities. The theoretical basis of such systems is the smart city concept, which has been briskly developed recently. It contains the principles of accessibility of public places, institutions, and establishments for people with special needs. In this work, it is analyzed the well-known algorithms for building optimal routes and available information services and mobile applications that solve the problem of visualizing public places and institutions with inclusive access and paving optimal routes to them.Keywords: inclusive access, optimal routing, shortest path search algorithms.
Keywords: inclusive access, optimal routing, shortest path search algorithms